Beyond Translated vs. Indigenous: Turkish Protestant Christian Hymnody as Global and Local Identity - Perigo, Jeremy (Religions, 2021)
At Turkey’s first national worship conferences in 2011, a passionate debate arose on whether Western music or indigenous Turkish music was most appropriate for worship. Some Turks felt that the Western missionaries were imposing indigenous musics on Turks as a type of "reverse colonization". They felt that the current Western musical styles were best for worship. One Turk stated, "the saz is being forced down our throats". Other Turks felt liberated to sing and play songs in traditional Turkish musical styles. The debate at the conference highlights the desire of missionaries and Turks to see renewal in congregational hymnody. Nevertheless, the Western vs. indigenous Turkish music debate reduces complex historical, musical, and liturgical issues into a divisive binarism. Using hymns sung in corporate worship in Turkey as a source, I will analyze here the quantity of musical localization in Turkish Protestant worship seeking to present musical localization as a lens to examine Turkish Christian liturgical identity.